78692mini
78692mini 78692mini
  • 01-01-2024
  • Mathematics
contestada

Simplify this expression:
2 (m-11m)-m+10=​

Respuesta :

myrieosman
myrieosman myrieosman
  • 01-01-2024

explanation step by step

2(m-11m)-m+l0. 2m-22m-m+10 -20m-m -2m+10= -21m+10

Answer Link

Otras preguntas

list the 6 characteristics of american economy and explain how they help the economy grow
solve the formula for the indicated variable  c=yt+y,for t (the solution is t=___)
What is the base of Apothecary
what are the components of blood?
An atom of which element has the strongest attraction for electrons? A) Ba B) Cs C) O D) F
Solve the simultaneous equations 2x+3y=-3 3x-2y=28
list the 6 characteristics of american economy and explain how they help the economy grow
which areas were obtained after the revolutionary war?
What are some behavioral adaptations for a porcupines?
solve the formula for the indicated variable  c=yt+y,for t (the solution is t=___)